Analisis Konsep Kompetensi Kepribadian Guru PAI menurut Az-Zarnuji - Muhammad Anas Ma'arif (ISTAWA, 2017)
PAI teacher personality competence is one of the factors that make the success and failure of educational activities therefore educators must develop their personality competencies in order to become tauladan learners. For that personality competence that existed in the book ta`limul muta`allim work of Imam az-Zarnuji should be realized by educators today such as, seriously, keep ablution and istiqomah night prayer. Thus this study aims to analyze the personality competence of teachers PAI more depth in order to be used as a reference of teachers today.